Twenty K.R. Narayanan orations: Essays by eminent persons on the rapidly transforming Indian economy - Raghbendra Jha (ANU Press, 2021)
The Australia South Asia Research Centre (ASARC) was established in 1994 in one of the premier universities of the world - The Australian National University (ANU). Apart from its research and doctoral training activities, ASARC also needed a public forum with a global reach to involve the best minds working on economic development in India as well as to honour its founder, Dr K.R. Narayanan, President of the Republic of India. The K.R. Narayanan Oration series was developed in response to these twin needs. The first oration was held in 1994 and the latest (the 20th) was held in 2018. The first 10 orations were published by ANU Press in 2006. This new edition updates the volume to include all 20 orations delivered so far and provides an updated introduction. All these orations have been delivered by leading academics, scientists and policymakers deeply involved in the transformation of the Indian economy. This collection of the Narayanan Orations is thus at once both an expert account of key aspects of the economic development process in India and a peek into India's potential in the future. As such, the publication of this volume marks a watershed in the intellectual debate on India's economic reforms program and should be welcomed by all those interested in the economic development of the country.
Keywords: 330; India; Space program; Food security; Blue Economy; Entwicklung; Wirtschaftsreform; Wirtschaftspolitik; Nachhaltige Entwicklung; Indien